Creating Resilient and Creative Human Resources for MSME Actors in Perk. Bukit Lawang Village - T. Muhammad Adriansyah; Daniel Yusuf; T. Elfira Rahmayati; Siti Asyraini; Fahriani Astuti Sitepu (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are one of the business units that play an important role in driving economic growth. This is because MSMEs contribute to employment absorption, play a role in income distribution, and serve as a socio-economic platform for the community. The strategic role of MSMEs as a pillar of the people’s economy lies in their great potential to stimulate community economic activities and simultaneously become a primary source of income for most people in improving their welfare. This study aims to examine how MSME capital and business management are carried out, as well as human resource development strategies for MSME actors in Perk. Bukit Lawang Village. The results of this study indicate that MSME actors in Perk. Bukit Lawang manage business capital by implementing capital planning strategies and recording transactions manually. In managing their businesses, MSME actors in Perk. Bukit Lawang apply several strategies, namely product quality, pricing, location, and promotion strategies. Furthermore, the strategies of the local government in developing human resources for MSME actors include mentoring programs, training, business capital assistance, and the provision of work equipment.